Cognitive impairment in bipolar disorder: neurodevelopment or neurodegeneration? An ECNP expert meeting report. - Goodwin, G; Martinez-Aran, A; Glahn, D; Vieta, E (2008)
This is a report arising from an ECNP expert meeting. Recent studies have focussed on cognitive problems in manic-depressive illness and a few have addressed premorbid neuropsychological functioning. The results are not fully consistent but seem to point to a neurodegenerative model, rather than a neurodevelopmental one, for some cognitive domains. There is agreement that cognitive dysfunction is highly correlated with psychosocial functioning. The neurobiological and clinical implications of recent findings will be discussed. Treatments to reduce subsyndromal symptoms and relapses may indirectly improve neurocognitive deficits and this should be better documented. Moreover, neurocognitive impairment in bipolar disorder should be considered a potential therapeutic target, so that research should focus on new drugs and psychological interventions, including neurocognitive rehabilitation, addressed to improve not only the cognition but also the functional outcome of this population.